Embracing quiet ego for flourishing: mediating role of authenticity and voluntary simplicity - Rabindra Kumar Pradhan; Peeyush Anand; Kailash Jandu; Shilpa Sabu; Adnaan Ahmad (Cogent Psychology)
This research examined the direct effect of the quiet ego on flourishing while also exploring the mediating role of authenticity and voluntary simplicity (VS) in the relationship between the quiet ego and flourishing. A cross-sectional survey research design was used in the current study. The study consisted of 580 participants employed through a purposive sampling strategy from various parts of India. The variables of the study were measured through standardized instruments. The data were analyzed through Statistical Package for Social Sciences 26.0 and Analysis of Moment Structures Software Tools. Results revealed that the quiet ego had a significant direct effect on flourishing. Furthermore, authenticity and VS were found to partially mediate the relationship between quiet ego and flourishing. Having an ego whose volume is tapered down, leading an authentic life, and adopting a lifestyle characterized by ethical consumerism are all linked to a better flourishing state.